Protaspid larvae are unique to trilobites - Lerosey-Aubril, Rudy; Laibl, Lukáš (Arthropod structure & development, 2021)
Trilobites represent a model for 'evo-devo' studies in fossil euarthropods, owing to a rare developmental trait: the biomineralization of the dorsal exoskeleton soon after hatching. Many fossilized trilobite ontogenies thus feature early stages - the protaspides - characterized by non-articulated, calcified dorsal exoskeletons. The recent discovery of a protaspid-like fossil occurring with aglaspidid remains in Middle Ordovician strata of Siberia has been interpreted as evidence for the presence of protaspides in these distant relatives of trilobites. In this contribution, we demonstrate that this Siberian protaspis actually belongs to the asaphid trilobite Isotelus (or a related taxon), a genus likely present in the same bed. We conclude that protaspid larvae still represent a developmental trait unique to Trilobita.
Keywords: Animals; Trilobita; Euarthropoda; Arthropods; členovci; zvířata; Larva; Larval ecology; Protaspis; Fossils; Ordovician; Aglaspidida; zkameněliny; larva